Environmental and Socioeconomic Indicators for Bioenergy Sustainability as Applied to Eucalyptus - Virginia H. Dale; Matthew H. Langholtz; Beau M. Wesh; Laurence M. Eaton (International Journal of Forestry Research)
Eucalyptus is a fast-growing tree native to Australia and could be used to supply biomass for bioenergy and other purposes along the coastal regions of the southeastern United States (USA). At a farmgate price of $66 dry Mg−1, a potential supply of 27 to 41.3 million dry Mg year−1 of Eucalyptus could be produced on about 1.75 million ha in the southeastern USA. A proposed suite of indicators provides a practical and consistent way to measure the sustainability of a particular situation where Eucalyptus might be grown as a feedstock for conversion to bioenergy. Applying this indicator suite to Eucalyptus culture in the southeastern USA provides a basis for the practical evaluation of socioeconomic and environmental sustainability in those systems. Sustainability issues associated with using Eucalyptus for bioenergy do not differ greatly from those of other feedstocks, for prior land-use practices are a dominant influence. Particular concerns focus on the potential for invasiveness, water use, and social acceptance. This paper discusses opportunities and constraints of sustainable production of Eucalyptus in the southeastern USA. For example, potential effects on sustainability that can occur in all five stages of the biofuel life cycle are depicted.